4개 대칭배열 발열 전자소자에서의 확산 열저항 산정 - 김윤호; 김서영; 이광훈 (대한설비공학회, 2006)
We propose the correlation to predict the spreading thermal resistance on a plate with symmetrical four heat sources. The correlation transforms four heat sources to a single equivalent heat source and then the spreading thermal resistance can be obtained with the existing equation for a single heat source. When the four heat sources are mounted on a square base plate, the correlation is expressed as a function of the heat source size, the length of base plate, the plate thermal conductivity and the distance between heat sources. Compared to the results of three-dimensional numerical analysis, the spreading thermal resistance by the proposed correlation is in good agreement within 10 percent accuracy.